The Juridical Analysis Related to the Compensation System in Land Procurement for the Construction of PLTU Batang - Lukmana, Hendra Adi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
Land has an important function in supporting human activities and needs, this makes land have high economic value, including in terms of land acquisition for public purposes. The implementation of compensation in the procurement of land for the Batang PLTU construction still ignores the value of economic losses and the value of land prices that are developing in the community. This article uses a normative juridical method. based on the studies conducted, it can be seen that legally the implementation of compensation for land acquisition for the construction of PLTU in Batang has not been carried out according to the mandate of Pancasila and the 1945 Constitution of the Republic of Indonesia, especially Article 33, this is because land compensation in the PLTU project does not see the value of land prices that apply sociologically in society. Keywords: Analysis; Compensation; Procurement.